Entropy analysis of magnetized ferroﬂuid over a vertical ﬂat surface with variable heating - Hanifa, Hanif; Sharidan, Shafie; Noraihan Afiqah, Rawi; Abdul Rahman, Mohd Kasim (Elsevier B.V., 2023)
This research analyzes the entropy generation in a two-dimensional flow of magnetized ferrofluid with variable wall temperature in the presence of heat generation. The mathematical model is designed to consolidate cylindrical-shaped Fe3O4-nanoparticles in pure water. An implicit finite difference is used to obtain the desired numerical solutions. The effects of nanoparticle volume concentration, magnetic parameter, heat generation, and power index on fluid velocity, temperature, entropy generation, and Bejan number are illustrated graphically. The entropy generation increased when the Brinkmann number increased; however, it decreased when the temperature difference decreased. For the authenticity of the current research, the obtained findings are compared with the previously existing results under certain conditions, and a good coexistence is achieved.